2001
DOI: 10.1292/jvms.63.723
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of Pestivirus RNA Detected in Live Virus Vaccines for Human Use.

Abstract: ABSTRACT. Live virus vaccines for human use, 29 monovalent vaccines against measles, mumps, rubella or polio, eight polyvalent vaccines against measles-mumps-rubella and one bacterial polyvalent vaccine against Streptococcus pneumoniae, were tested by reverse transcriptase-nested PCR for the presence of petivirus or pestivirus RNA. Twenty-four samples were selected from European manufacturers, ten were from U.S.A. and four from Japan. Five (13.1%) out of 38 tested samples were positive for pestivirus RNA. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 43 publications
0
16
0
2
Order By: Relevance
“…The results of the PNS method are essentially qualitative and provide the exact species classification of an isolate, although they offer no percentage values for homology among species and genotypes. According to the PNS method, the BVDV-1 species have been segregated into fourteen genotypes [10,15,16]. The taxonomic status of a giraffe strain was characterized, based on the 5'-UTR, as a new cluster among Pestivirus species [12].…”
Section: Bovine Viral Diarrhea Virus 2 (Bvdv-2) Represents An Establmentioning
confidence: 99%
“…The results of the PNS method are essentially qualitative and provide the exact species classification of an isolate, although they offer no percentage values for homology among species and genotypes. According to the PNS method, the BVDV-1 species have been segregated into fourteen genotypes [10,15,16]. The taxonomic status of a giraffe strain was characterized, based on the 5'-UTR, as a new cluster among Pestivirus species [12].…”
Section: Bovine Viral Diarrhea Virus 2 (Bvdv-2) Represents An Establmentioning
confidence: 99%
“…Noncytopathic biotypes of BVDV have been identified in commercially available lots of fetal bovine serum despite testing by the manufacturer (6,45). Consequently, BVDV has been identified in commercially available bovine, canine, feline, and primate cell lines (16,19), human viral vaccines for measles-mumps-rubella (18,21), and interferons for human use (20). Viral contamination of biologicals for human use may be the reason BVDV-specific antibodies have been found in some samples of human serum (17).…”
mentioning
confidence: 99%
“…Similarly, interferon for human use was found contaminated by BVDV-1 RNA [31]. Further studies demonstrated the occurrence of Pestivirus contamination in live virus vaccine for human use also in Europe [30]. The characterization, based on primary nucleotide sequence homology and secondary palindromic sequence structure in the 5'-UTR, revealed positive samples contaminated with the BVDV-1 genotype Ib.…”
mentioning
confidence: 93%
“…Other particularly important aspects related to the potential of iatrogenic infections are the possible contamination of modified live vaccines and the capacity of pestiviruses to cross placental barrier and determine vertical transmission [30]. Therefore, a definitive risk during pregnancy has to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation